Tindak Tutur Komisif Dan ImplikaturWacana Spanduk Caleg DPRD 2014 di Lingkungan Surakarta - Firmana, Akhmad Farid, Prof. Dr Harun Joko Prayitno M. Hum, Dra Atiqa Sabardilah, M.Hum (2017)
The purpose of this study was to describe the form of speech acts commissive discourse banners Candidates for the Legislative Council in the Surakarta, describe the form implicatures discourse banners Candidates for the Legislative Council in the neighborhood of Surakarta, and describe what is contained in the speech acts commissive and shape implicatures discourse banners Candidate Legislative Member parliament in Surakarta environment. Data collection techniques in this study using techniques of documentation, see, and technical notes. The validity of the data in this study using triangulation theory. Data were analyzed using an extra match lingual. Model analysis and match method consists of techniques appeal equalize circuit (HBS) and the circuit appeal differentiate (HBB). These results indicate that the speech act commissive diklarifikasiakan by 1. The form of speech acts in discourse banner commissive DPRD candidates that includes (a) speech acts commissive intend, (b) speech acts Komsif swear (c) speech acts commissive promise and (d) follow said commissive offer. 2. Form the discourse implicature banner Parliament candidates. Implicature clarified (a) conventional implicature and (b) non-conventional implicatures. 3. Purpose commissive form of speech acts and implicatures discourse banners Council candidates will be clarified intent commissive form of speech acts (a) plans, (b) swearing, (c) pledges, (d) offer and intent form implicature (a) conventional implicatures (b ) non-conventional implicatures.